Automatic Attendance System Using Facial Detection and Recognition Technique (International Journal of Engineering and Computer Science, 2018)
A lot of precious time is wasted in taking attendance in schools, universities and other training institutes. Although the process of taking attendance may seem to be very simple and an easy task, the irony lies in the fact that this easy process is tiresome and grueling routine. In this paper, I propose a framework that takes the participation of students in the classroom lecture. The proposed system framework takes the participation naturally utilizing face identification and recognition. This participation is recorded by utilizing a camera connected in the classroom that is continuously catching pictures of students, detect the faces in the image and contrast the distinguished appearances and the database and mark the attendance. This paper first audits the related works in the field of participation administration and face acknowledgment.At that point, it presents our framework structure and plan. Finally, experiments are implemented and it shows the improvement of the performance of the attendance framework.